Relationship between The Adsorption Capacity of Pesticides by Wood Residues and The Properties of Woods and Pesticides - Rodriguez-Cruz, Sonia; Andrades, Maria S.; Sanchez-Camazano, Maria; Sanchez-Martin, Maria J. (Environmental Science & Technology, 2007)
With the aim to explore the potential use of wood residues in technologies aimed at preventing the pollution of soil and water, we studied the adsorption of four non-ionic pesticides (linuron, alachlor, metalaxyl, and chlorpyrifos) and two ionic pesticides (dicamba and paraquat) with a Kow range of ?4.5 to 4.7 by nine types of wood with lignin content in the 18.2?26.9% range. The Freundlich Kf values were considered as indicators of the adsorption capacity. A statistical study was carried out using simple and multiple correlations to establish the degree to which the different parameters of the woods and of the pesticides were involved in adsorption. In the case of the non-ionic pesticides, positive and negative significant correlations were observed between Kf and the lignin (r = 0.73?0.83, p < 0.05?0.01), and soluble C contents of the woods (r = 0.66?0.84), p < 0.1?0.01). For dicamba, a correlation between Kf and pH (r = ?0.66, p < 0.1) of the woods was found, while for paraquat, this was seen between Kf and the cation exchange capacity (r = 0.71, p < 0.1) of the woods. No significant correlation was observed between Kf and the total C content of the woods. A highly significant correlation between Kf and Kow values (r ≥ 0.93, p < 0.01) was found in the adsorption of the pesticides by the woods (with the exception of paraquat) showing that this parameter is very important in this adsorption process. The determination coefficient of the multiple correlation between Kf and the parameters Kow, soluble C, and lignin contents accounts for nearly 100% of the variability in adsorption for non-ionic pesticides. Based on the results of our study and of those of the literature related to the adsorption of aromatic hydrocarbons, we used the Kow values to define a predictive model of adsorption of hydrophobic organic compounds in general by the woods.
doi: 10.1021/es062616fdoi: 10.1021/es062616fThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: lignin content; pesticide adsorption; wood properties (voyant); wood residues